Description and host interactions of a new species of Exetasis Walker (Diptera: Acroceridae), with a key to species of the genus - Barneche, Jorge Adrian; Gillung, Jéssica Paula; González, Alda (Zootaxa, 2013)
Exetasis jujuyensis Gillung sp. nov. (Acroceridae) is described from Argentina and a dichotomous key to species of Ex-etasis Walker is provided. Detailed observations are presented on the effect of fly larval development on the behavior of the host spider (Acanthoscurria sternalis Pocock (Theraphosidae)).